Increased Intracranıal Pressure Syndrome - Şen, Yaşar; Taşkın, Erdal; Kabakuş, Nimet (Fırat University, 2001)
Intracranial hypertension results from an increase in the volume of the cranial cavity. The clinical signs and findings in children may change according to the patient's age and disease course. It should be rapidly diagnosed and treated because of the ıts serious complications.

Kafa içi basınç artışı, intrakranial kompartmanların volümündeki bir artış sonucu meydana gelmektedir. Çocuklardaki klinik belirti ve bulgular hastanın yaşı ve gelişim hızına göre değişiklik gösterir. Ciddi komplikasyonları nedeni ile acil tanı ve tedavi gerektirmektedir.
KAFA İÇİ BASINÇ ARTIŞI SENDROMU